2013
DOI: 10.4303/jdar/235709
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Blocks the Depressogenic Effects of Alcohol: Implications for Drinking-Smoking Co-Morbidity

Abstract: Alcohol and nicotine are two very commonly abused legal substances. Although various hypotheses for such co-dependence have been suggested, it is not known whether the effects of alcohol and nicotine on mood behavior may also contribute to such co-abuse. Chronic exposure to high alcohol levels may lead to various neurochemical changes and precipitate depressive-like behavior. Nicotine, on the other hand, may exert an antidepressant-like effect. Here, we sought to determine whether nicotine may also block or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…An observer who was blind to the experimental conditions of the animals scored each behavioral event as mobility if there were swimming or upward-directed climbing movements, and immobility was scored when there was a total lack of movement or the animal displayed only enough activity to keep its head above water. Behavioral observations from each 5-second epoch of the test were summated, and the percent immobility (# immobility events/total # events × 100) was calculated for each animal [39, 40]. …”
Section: Methodsmentioning
confidence: 99%
“…An observer who was blind to the experimental conditions of the animals scored each behavioral event as mobility if there were swimming or upward-directed climbing movements, and immobility was scored when there was a total lack of movement or the animal displayed only enough activity to keep its head above water. Behavioral observations from each 5-second epoch of the test were summated, and the percent immobility (# immobility events/total # events × 100) was calculated for each animal [39, 40]. …”
Section: Methodsmentioning
confidence: 99%
“…Conversely, alcohol preferring (AA) rats may exhibit depressive-like characteristics following voluntary alcohol intake compared to alcohol non-preferring (ANA) rats (Viglinskaya et al 1995). Although various theories have attempted to explain the association between AUD and depression, it appears that a number of factors, including genetic predisposition and alterations in neurochemical substrates, such as the noradrenergic system, may contribute to this co-morbidity (Balsamo et al, 2016; Bravo et al, 2017; Donadon and Osorio, 2016; Getachew et al, 2010; Jung et al, 2016; Kalejaye et al, 2013; Merikangas and Gelernter, 1990; Ovestreet et al, 2005; Rezvani et al, 2002, 2007; Rincon-Hoyos, et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This might be partially due to the very complex phenomenon of addiction as well as lack of full understanding of the pharmacodynamics of alcohol and nicotine. Nonetheless, it is evident that genetics, various receptor systems (including nicotinic cholinergic) as well as interactions of alcohol and nicotine with the neurotrophic factors, particularly brain-derived neurotrophic factor (BDNF), may play a significant role in their co-use [ 1 , 2 , 3 , 4 ]. In addition, some of the opposite pharmacological actions of these two substances, for example, sedative and depressogenic effects of alcohol [ 1 , 5 ], versus nicotine’s stimulant and antidepressant effects [ 5 , 6 , 7 ] are likely to entice the heavy drinker to smoke in order to counter some of the negative effect associated with high alcohol intake.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of the opposite pharmacological actions of these two substances, for example, sedative and depressogenic effects of alcohol [ 1 , 5 ], versus nicotine’s stimulant and antidepressant effects [ 5 , 6 , 7 ] are likely to entice the heavy drinker to smoke in order to counter some of the negative effect associated with high alcohol intake. Indeed, we have provided evidence that the depressogenic effect of alcohol in rats can be blocked by nicotine [ 2 ]. Moreover, we and others have reported that the depressogenic effect of alcohol is associated with a reduction in the hippocampal BDNF [ 1 , 2 , 8 ], which was also reversed by nicotine [ 2 ].…”
Section: Introductionmentioning
confidence: 99%